Detecting incised valley-fill sandstone in Beauchamp field by using seismic attributes, Stanton County, USA - Almalki, Saad Abdullah (Kansas State University, 2013)
A 3D seismic survey was conducted on Beauchamp, Beauchamp North and Beauchamp Northwest fields, which are located in Stanton County, southwest Kansas, by Berexco, Inc. Stanton County is situated on the Hugoton embayment which is the shelf of the Anadarko basin. The producing formation in this area is the Morrow formation, which is the lower Pennsylvanian period. The Morrow formation is mostly a clastic unit and its base was transgressive marine. It is considered an unconformity lying on the Mississippian rocks. Wide geologists agreed with the name of Morrow as name in the rock stratigraphic sequence in the study area (Forgotson, et al., 1966). "The Morrowan series is defined as the interval between the base of the Atokan Thirteen finger limestones and the top of the pre-Pennsylvanian unconformity" (Puckette, et al., 1996). The depositional environment of upper Morrow Formation in western Kansas, according to Sonnenberg (1985), Krystinik et al (1990), was a valley-fill deposit. The purpose of this study is to focus on detecting valley-fill sandstone in the study area by using appropriate seismic attributes. Coherence and discontinuity along dip succeeded to map incised valley-fill sandstone width. On another hand, spectral decomposition displayed subtle changes in incised valley thickness. Positive curvature shows valley edges in moderate resolution, but the most negative curvature wasn't clear enough to display the valley-fill sand. The result of RMS amplitude and average energy attributes results were almost the same. They exhibited four areas of high amplitude and energy in the valley which may indicate the presence of hydrocarbon. Sweetness and envelope amplitude both detected the valley in the study area. A gamma ray cross section shows that there are sequences of incised valley-fill sandstone which are sandstone A, B, C and D of the upper Morrow formation. Johns 2-12 well is producing oil from lower Morrow and sandstone A, thus the valley in the study area may produce oil from Sandstone A or B as RMS amplitude and average energy showing high amplitude in four areas in the valley.
Keywords: Valley-fill sandstone; Seismic attributes; Morrow formation; Geophysics (0373)